Literature and Cultural Policy through the Pages of Leitura - Rio Doce, Cláudia (Revista do Instituto de Estudos Brasileiros, 2012)
The journal Leitura was a bibliographic bulletin which was firstpublished in Rio de Janeiro in the early 1940s, with the objectiveof popularizing literature (hence becoming part of the Braziliancultural policy of the time). To this purpose, it promotes certain ideassuch as the rapprochement between the artist and the people, and thedemocratization of art, thus resulting in a series of adaptations madeby the own journal or diffused in it, including translations, novelsummaries, explanations of works by the authors themselves or bytheir peers. This paper intends to verify some of the conflicts thatarise in its pages at the first years of its publication.